VMAT monthly QA using two techniques: 2D ion chamber array with an isocentric gantry mount and an in vivo dosimetric device attached to gantry. Issue 2 (22nd April 2013) - Myers, P.; Stathakis, S.; Buckey, C.; Papanikolaou, N.
Abstract Purpose Varian RapidArc is a volumetric modulated arc therapy (VMAT) that obtains a conformal dose around the desired structure by employing variable gantry speed, dose rate and dynamic multileaf collimator (DMLC) speed as the gantry rotates about machine isocenter. This study is meant to build upon previous research by Ling et al. by completing the tests with an in vivo dosimetric device attached to the linac gantry and a 2D ionisation chamber array with an isocentric gantry mount. Materials and methods Two PTW detectors, seven29 array with gantry mount and DAVID, were attached to the linear accelerator gantry, allowing each device to remain perpendicular to the beam at all gantry angles. Three tests for RapidArc evaluation were performed on these devices including: dose rate and gantry speed variation, DMLC speed and dose rate variation and DMLC position accuracy. The reproducibility of the arc data was also reported. Results A picket fence plan varying dose rates (111 to 600 MU/minute) and gantry speeds (5·5 to 4·3°/second) was delivered consisting of seven sections of different combinations. These measurements were compared with static gantry, open field measurements and found to be within 2·39% for the DAVID device and 0·84% for the seven29. A four-section picket fence of varying DMLC speeds (0·46, 0·92, 1·84 and 2·76 cm/second) was similarly evaluated and found to be within 1·99% and 3·66% for the DAVID and seven29, respectively. For DMLC position accuracy, a picket fence arc plan was compared with a static picket fence and found to agree within 0.38% and 2.91%. Reproducibility for these three RapidArc plans was found to be within 0·30% and 2·70% for the DAVID and seven29. Conclusion The DAVID and seven29 detectors were able to perform the RapidArc quality assurance tests efficiently and accurately and the results were reproducible. Periodic verification of DMLC movement, dose rate variation and gantry speed variation relating to RapidArc delivery can be completed in a timelier manner using this equipment.